Análise da propagação de trinca por fadiga submetida a carregamento cíclico com razão de carga negativa para a liga AA 6005 - Silva, Bárbara Rezende Leite [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
For engineering projects requiring a high degree of reliability, it is necessary to understand, in addition to the physical and chemical properties of the materials, its limits for static and dynamic applications, in order to guarantee structural integrity and safety. The Fadiga study is a project item of great importance. Fatigue life comprises nucleation and the propagation of cracks, and most of life can be consumed during propagation. Many models and theories have been proposed in order to understand and predict the crack propagation behavior in fatigue. In this context, fatigue cracking propagation involving loading with negative R has generated discussions and controversies about the influence of the compressive load as a driving force in the crack propagation. Some researchers assume that the compressive part of the cyclic loading has no influence on the crack growth. In addition, the industry is increasingly using aluminum alloys in its projects. AA 6005 series alloys have good fatigue, corrosion and weldability. They are applied in railway and bus structures, structural engineering, towers, platforms and pipelines. In this work, fatigue crack propagation tests were performed on specimens with initial central pre-crack for R = -1 and R = 0 for the same maximum loads on the AA6005 aluminum alloy. The results showed that the negative part of the load influenced the propagation rate of the fatigue crack, mainly for larger cracks sizes and smaller loads

Para projetos de engenharia que exigem alto grau de confiabilidade, é preciso compreender, além das propriedades físicas e químicas dos materiais, seus limites para aplicações estáticas e dinâmicas, a fim de garantir segurança e integridade estrutural. O estudo de Fadiga é um item de projeto de grande importância. A vida em fadiga compreende nucleação e a propagação de trincas, sendo que a maior parte da vida pode ser consumida durante a propagação. Muitos modelos e teorias têm sido propostos a fim de compreender e prever o comportamento de propagação da trinca em fadiga. Neste contexto, análises de propagação de trincas por fadiga envolvendo carregamento com R negativo têm gerado discussões e controvérsias sobre a influência da carga compressiva como força motriz na propagação da trinca. Alguns pesquisadores assumem que a parte compressiva do carregamento cíclico não tem influência no crescimento da trinca. Além disso, a indústria vem utilizando, cada vez mais, as ligas de alumínio em seus projetos. As ligas da série AA 6005 possuem boa resistência à fadiga, à corrosão e soldabilidade. São aplicadas em perfis de estruturas ferroviárias e de ônibus, engenharia estrutural, torres, plataformas e gasodutos. Neste trabalho foram realizados ensaios de propagação de trinca por fadiga em corpos de prova com pré-trinca central inicial para R=-1 e R=0 para as mesmas cargas máximas na liga de alumínio AA6005. Os resultados mostraram que a parte negativa do carregamento influenciou na taxa de propagação da trinca por fadiga, principalmente para tamanhos de trincas maiores e carregamentos menores
Analysis of fatigue crack propagation subjected to cyclic loading with negative charge ratio for alloy AA 6005
Keywords: Mecânica da fratura; Ligas de aluminio; Fadiga; Fracture mechanics